Konsep Geometri Bangun Datar Pada Artefak Dan Relief Candi Plaosan - Gunawan (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
This research aims to explore the concept of geometry in mathematics in schools related to Plaosan Temple. This research was conducted at Plaosan Temple from January to July 2023. This research is descriptive qualitative research with an ethnographic approach. This research was carried out through observation, documentation and interviews to collect data. Observations were carried out directly at Plaosan Temple. Plaosan Temple is divided into two complexes, namely Plaosan Lor Temple and Plaosan Kidul Temple. Plaosan Temple is also nicknamed the twin temples. In the Plaosan Lor Temple complex there are several buildings including the main temple, Perwara Temple, Perwara Stupa, Mandhapa, Perwara Mandhapa Stupa, Fence, Kori Agung Gapura, and Dwarapala Statue. The informants in this research were cultural figures under the Central Java Cultural Heritage Preservation Center and junior high school mathematics teachers in Gunung Kidul. The data analysis technique in this research uses the Spradley model data analysis technique. The result of this research is the discovery of geometric concepts, especially flat-sided shapes in the Plaosan Lor Temple Complex, namely, triangle models, trapezoid quadrilaterals, rhombuses and parallelograms. From the geometric model of flat-sided spatial shapes, the concept of flat-sided spatial shapes was found in the artifacts and reliefs of Plaosan Temple Keywords: Ethnomathematics, Mathematics Learning, Geometry, Flat Side Building